The prevalence of rheumatic diseases in central Greece: a population survey - Anagnostopoulos, Ioannis (BioMed Central, 2010)
BACKGROUND: Rheumatic diseases are a major health and financial burden for societies. The prevalence of rheumatic diseases may change over time, and therefore, we sought to estimate the prevalence of rheumatic diseases in an adult population of central Greece. METHODS: In this prospective cross-sectional population survey, a random sample of adult population was drawn from poll catalogues of a region in central Greece. A postal questionnaire was sent to 3,528 people for the presence of any rheumatic disease. All positive cases were further confirmed by clinical examination using the American College of Rheumatoloy criteria. Multiple regression analysis was used to assess risk factors for rheumatic diseases. RESULTS: The response rate was 48.3% (1,705 answers). Four hundred and twenty individuals (24.6%) had a rheumatic disease. The prevalence of rheumatoid arthritis was 0.58% (95% confidence interval [CI], 0.32-0.87), of psoriatic arthritis was 0.35% (95% CI, 0.33-1.13), of ankylosing spondylitis was 0.29% (95% CI, 0.28-0.94), of primary Sjögren's syndrome was 0.23% (95% CI, 0.22-0.75) and of systemic lupus erythematosus was 0.11% (95% CI, 0.11-0.37). One individual had systemic sclerosis (prevalence, 0.058%), 1 individual had dermatomyositis (prevalence, 0.058%; 95% CI, 0.05-0.18), 2 individuals had vasculitis (prevalence 0.11%; 95% CI, 0.11-0.37), 81 individuals had gout (prevalence, 4.75%; 95% CI, 4.41-5.13), and 304 individuals had osteoarthritis (OA) (prevalence 17.82%; 95% CI, 16.50-19.34). Gout was associated with male gender, diabetes mellitus, and hypertension, and OA was associated with age, female gender, and hypertension. CONCLUSIONS: Rheumatic diseases are common in central Greece, affecting nearly a quarter of adult population. OA and gout are the most common joint disorders.